2021
DOI: 10.1002/jcla.23957
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 and Beclin1 levels in Polycystic Ovary Syndrome

Abstract: Background Sestrin2 and beclin1 are two newly found proteins that have essential roles in autophagy. This study attempted to evaluate the plasma concentrations of sestrin2 and beclin1 in women with polycystic ovary syndrome (PCOS) and healthy controls and to explore the clinical value of these proteins as novel biomarkers for PCOS. Methods In this case‐control study, plasma levels of sestrin2 and beclin1, fasting blood sugar (FBS), lipid profile, insulin, and androgens were evaluated in 63 women (31 patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…However, extensive laboratory tests, including serological tests and cerebrospinal uid analysis, effectively ruled out these infectious causes. The investigation also took into account metabolic disorders, which can be associated with neuropsychiatric symptoms and calci cations (2,9). Conditions like Wilson's disease, hypoparathyroidism, and mitochondrial disorders were evaluated but ultimately excluded through appropriate laboratory tests such as copper studies, parathyroid hormone levels, and liver function tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive laboratory tests, including serological tests and cerebrospinal uid analysis, effectively ruled out these infectious causes. The investigation also took into account metabolic disorders, which can be associated with neuropsychiatric symptoms and calci cations (2,9). Conditions like Wilson's disease, hypoparathyroidism, and mitochondrial disorders were evaluated but ultimately excluded through appropriate laboratory tests such as copper studies, parathyroid hormone levels, and liver function tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, inconsistencies are found in the studies. In a recent study on women with PCOS, plasma sestrin 2 levels were shown to be significantly lower than in healthy controls [ 38 ], and higher in another study [ 16 ]. In this study, nonobese and obese women with PCOS were separated and compared in terms of sestrin 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that disorders related to autophagy, a stress-induced lysosome-mediated degradation process, cause insulin resistance. In addition, dysregulation of autophagy was observed in the ovarian granulosa cells and endometria of women with PCOS [ 8 ]. It is also thought to be associated with increased oxidative stress and insulin resistance in PCOS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation